Making the case for Temporary Migrant Worker Programmes: Evidence from the UK's rural guestworker ('SAWS') scheme. (August 2015) - Scott, Sam
Abstract: The UK has had a Temporary Migrant Worker Programme (TMWP) for agricultural 'guestworkers' since 1943. Most recently referred to as the Seasonal Agricultural Workers Scheme (SAWS), SAWS accommodated 25, 000 workers per annum by its 2004 peak. However, the UK government then announced the scheme's closure (initially for 2011, but then delayed until 2014). This paper examines employers' response to this closure and, specifically, juxtaposes the academic critiques of TMWPs with the very strong employer preference for them. This preference, the paper concludes, is about the way in which TMWPs allow labour to be more readily and more extensively controlled, and, also allow employers access to 'better quality' workers. Considering these benefits of quality and control, alongside the academic critiques, the paper concludes that SAWS should be retained, but with major changes and safeguards. Highlights: The paper advances our understanding of recent rural demographic change as a result of rising international labour migration. This is the first academic appraisal of the UK's Seasonal Agricultural Workers Scheme (SAWS was operational in the UK from 1943 to 2014). Empirically, the paper reviews the main UK policy documents pertinent to SAWS and analyses survey and interview-based research from employers who universally advocated the scheme. The paper compares this forceful pro-business case for TMWPs like SAWS with the equally strong academic critique of such schemes. The paper concludes by outlining what a new version of SAWS, following its closure in January 2014, could and should look like. To this extent, the paper cautiously supports well regulated and small-scale TMWPs.